Peran Guru Pendidikan Agama Islam dan Budi Pekerti dalam Membentuk Perilaku Sosial Siswa SMA Negeri 1 Waru - Humairoh, Siti; Yuliastutik, Yuliastutik; Marfiyanto, Tri (Lembaga Yasin AlSys, 2025)
This study explores the role of exemplary Islamic religious education teachers and morals in shaping students’ social behavior at SMA Negeri 1 Waru. Using a qualitative field approach with descriptive-qualitative-phenomenological methods, the findings highlight that teachers significantly influence students' attitudes and behavior by serving as role models. Teachers are not only educators of religious material but also exemplify integrity, noble morals, and responsibility, inspiring students to develop character traits such as integrity, responsibility, and social care. This is evident in vertical interactions with God, such as congregational prayers and dhikr, which enhance students’ spiritual awareness, and in social interactions, characterized by politeness, collaboration, and mutual support, creating a positive learning environment. Supporting factors include teacher integrity, parental involvement, peer influence, and school facilities and regulations that strengthen social behavior development. However, challenges arise from students’ diverse backgrounds and external global influences, requiring concerted efforts to promote exemplification among stakeholders. Ultimately, the role of teachers as role models not only shapes individual student behavior but also fosters a positive school environment and strengthens the school community at SMA Negeri 1 Waru.